EFFECT OF SWIM-UP AND GLASS WOOL TECHNIQUES, WITH ADDING ANTIOXIDANTS TO TRIS EXTENDER ON IMPROVING POST-CRYOPRESERVED TOTAL SPERM CHARACTERISTICS IN STRAW AND FREEZABILITY PERCENTAGE FOR LOW SEMEN QUALITY OF HOLSTEIN BULLS - & et al., Hassan (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2021)
This study was conducted to investigate the effect of swim-up and glass wool as sperm separation techniques with adding vitamin E and superoxide dismutase (SOD) to Tris extender on improving post-cryopreserved total sperm characteristics in straw and freezability percentage for low semen quality of Holstein bulls. Low and good of semen were extended using Tris extender. Good semen quality (GSQ) was divided into 3 groups (L1; Tris extender, L2; 2 mM vitamin E, L3; 200 IU SOD) Low semen quality (LSQ) was divided into two main groups, and subdivided into 3 sub-groups (L4; Tris extender, L5; 2 mM vitamin E, L6; 200 IU SOD). In the second main group, swim-up and glass wool techniques were used with adding vitamin E and SOD and subdivided into 3 sub-groups with each technique, and referred to L7, L8 and L9 for swim-up technique and L10, L11 and L12 for glass wool technique. Sperms with good motile intact acrosome and plasma membrane normal morphology of sperm were obtained using the glass wool separation technique with adding vitamin E.